Forvandle moralsk desperasjon til moralsk handlingsrom: Troens kraft (Tidsskrift for Praktisk Teologi, 2024)
It is a rare and precious gift to be alive as human beings at this crucible point in time. “The next five years may be the most important in human history,” declares a South African climate expert. Decisions and actions taken by human beings in the next few years will determine the fate of life on Earth.Never has the need to see clearly “what is going on” so that we may respond wisely borne more long-lasting and morally weighted consequences. Nevertheless, most of “us” (myself included) fail to face squarely the climate-related realities at hand and our role in them. This is most odd: Our house is burning. Though the fire has not yet reached our rooms, it is raging through many others’ rooms, and our children are in the house. Yet, we pour fuel on the fire.